2016
DOI: 10.1002/jcph.752
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Properties of Nintedanib in Healthy Volunteers and Patients With Advanced Cancer

Abstract: Nintedanib, a triple angiokinase inhibitor, has undergone clinical investigation for the treatment of solid tumors and idiopathic pulmonary fibrosis. Nintedanib (Vargatef ) plus docetaxel is approved in the EU for the treatment of patients with adenocarcinoma non-small cell lung cancer (NSCLC) after first-line chemotherapy, and as monotherapy (Ofev ) in the United States and EU for the treatment of patients with idiopathic pulmonary fibrosis. Pharmacokinetics (PK) of nintedanib after oral single and multiple d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 16 publications
(40 reference statements)
1
58
0
Order By: Relevance
“…The small percentage of Nintedanib absorbed in the gut is partially due to transport proteins activity (such as P-glycoprotein) and the first-pass hepatic metabolism. Nintedanib is rapidly absorbed and it achieves the maximum plasma concentration (Cmax) within 1-3 h after oral administration [29]. After food intake, Nintedanib exposure increases by approximately 20% compared to administration under fasting conditions (90% CI 95.3-152.5%).…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 4 more Smart Citations
“…The small percentage of Nintedanib absorbed in the gut is partially due to transport proteins activity (such as P-glycoprotein) and the first-pass hepatic metabolism. Nintedanib is rapidly absorbed and it achieves the maximum plasma concentration (Cmax) within 1-3 h after oral administration [29]. After food intake, Nintedanib exposure increases by approximately 20% compared to administration under fasting conditions (90% CI 95.3-152.5%).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Nintedanib is available as soft gelatin capsules of 100 and 150 mg. As summarized in Table 1, in a PK profile study in healthy volunteers, Nintedanib demonstrated a relative oral bioavailability of 4.7% (90% CI 3.62-6.08) [29]. The small percentage of Nintedanib absorbed in the gut is partially due to transport proteins activity (such as P-glycoprotein) and the first-pass hepatic metabolism.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 3 more Smart Citations